The Implementation of the Cooperative Model Reviewed from Motivation Towards Learning Achievement of Class XII Students at Guppi High School - Nur Aisyah; Hastuti Agussalim; Faathir Almur (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This type of research is an experimental research involving two experimental groups. The sample in this study was class XII. 1 as experimental class 1 and class XII. 2 as experimental class 2. Data were collected using questionnaires, tests, and observation sheets. The data were then analyzed descriptively and two-way analysis of variance (ANOVA) and continued with a post hoc test. The results of the study showed that (1) the average mathematics learning achievement of students using the Talk Stick cooperative learning model was 88.7 out of an ideal value of 100 with a very high category, (2) the average mathematics learning achievement of students using the Example Non-Example cooperative learning model was 87.6 out of an ideal value of 100 with a very high category, (3) there was a significant difference in mathematics learning achievement between students with high, medium, and low learning motivation with a significance of 0.001, and (4) there was no interaction between the cooperative learning model and motivation on mathematics learning achievement with a significance of 0.306.